Menjaga Nilai Pancasila Sebagai Identitas Nasional di Tengah Penetrasi Budaya Asing - Lily Nurananda Sari; Nurmanasari (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2026)
Pancasila, as the nation's identity, Pancasila holds important values as the national character and distinctive feature of the country. It stands out among other forms of identity as the nation's highest ideological value. Pancasila is unique compared to other identities, not merely a physical symbol but a psychological identity that reflects the character of Indonesia. This uniqueness, which is a characteristic of the nation, is often influenced by foreign cultures and globalization, often resulting in deviations. Therefore, efforts are being made to preserve the values of Pancasila so that they are not eroded by external cultural influences. A more in-depth analysis is needed to examine the influence of foreign cultures, and conceptual analysis methods are used as a guide to study this phenomenon. It is clear that in today's digital age, where everything is presented instantly, foreign cultures easily infiltrate the structure of social life, causing the erosion of idealistic values. Here are some ways to protect the values of Pancasila from foreign cultural erosion: (1) foster a strong spirit of nationalism, for example by encouraging love for domestic products and culture; (2) fostering love for the homeland; (3) instilling and practicing the values of Pancasila responsibly; (4) instilling and practicing religious values correctly; (5) being selective towards foreign cultural influences entering Indonesia; (6) strengthening and maintaining national identity so that it does not fade; and (7) strengthening Pancasila.